The Impact of Internet use Frequency on the Gender Role Concept of Chinese Residents: An Empirical Study based on CGSS2021 - Zhang, Xinyue (International Journal of Engineering and Management Research, 2024)
In the traditional society, the gender role concept of "men are the main outside, women are the main inside" restricts the individual development of women. There is no research to answer the question of the role of the Internet in the gradual change of gender role concepts. Based on this, this paper uses the data of the 2021 China General Social Survey (CGSS) to explore the impact of the use of the Internet on the gender role concept of Chinese residents. The results show that the higher the frequency of Internet use, the more equal the gender role concept of Chinese residents.